2014
DOI: 10.25011/cim.v37i5.22014
|View full text |Cite
|
Sign up to set email alerts
|

Adropin: A New Marker for Predicting Late Saphenous Vein Graft Disease after Coronary Artery Bypass Grafting

Abstract: Purpose: Saphenous vein graft disease (SVGD), defined as an occlusion of 50% or more of the SVG excluding distal anastomotic occlusion, is an important predictor of morbidity after coronary artery bypass grafting (CABG). Late graft occlusion is a serious complication that often limits the use of the saphenous vein as a coronary bypass graft. Late graft occlusion is particularly common in old, degenerated venous grafts with advanced atherosclerotic plaques. Adropin has been implicated in the homeostatic control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 13 publications
1
16
0
1
Order By: Relevance
“…Thus, downregulation of adropin in depression may contribute to impaired energy homeostasis in this disease [39]. Finally, low levels of circulating adropin is the predictor of late saphenous vein graft occlusion [40], suggesting that adropin deficiency may contribute to the pathogenesis of saphenous vein graft disease.…”
Section: Adropin In the Cardiovascular Systemmentioning
confidence: 99%
“…Thus, downregulation of adropin in depression may contribute to impaired energy homeostasis in this disease [39]. Finally, low levels of circulating adropin is the predictor of late saphenous vein graft occlusion [40], suggesting that adropin deficiency may contribute to the pathogenesis of saphenous vein graft disease.…”
Section: Adropin In the Cardiovascular Systemmentioning
confidence: 99%
“…Studies using mice suggest the peptide hormone adropin has metabolic (1-3) and vascular functions (4). Circulating adropin concentrations have been measured in several mammalian species using commercially produced enzyme immunoassays (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Human studies have screened for associations between plasma adropin concentrations and cardiovascular disease (5,8,12,17), endothelial function (10,11), type 2 diabetes (T2D) (7,9,14,17), obesity and aging (6), and exercise response (23).…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al (25) revealed that low serum adropin level was associated with hyperhomocysteinemia and more severe coronary atherosclerosis, as reflected by higher SYNTAX score. Demirçelik et al (10) revealed that adropin level is lower in patients with late saphenous vein graft occlusion and these reduced adropin levels. These studies suggested that adropin might have role on progression of atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, it was found that patients with stable ischemic heart disease have lower adropin concentrations (9). Also, Demirçelik et al (10) reported that adropin level is lower in patients with late saphenous vein graft occlusion.…”
Section: Introductionmentioning
confidence: 98%